2013
DOI: 10.3892/mco.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Survival study and clinicopathological evaluation of trichilemmal carcinoma

Abstract: Abstract. Trichilemmal carcinoma (TC) is a rare malignancy, commonly located on the scalp, forehead and neck, trunk or the upper extremities. The aim of this study was to investigate the clinicopathological characteristics and prognostic factors of TC, and to determine an optimal treatment strategy for these patients. Consecutive patients who were admitted to the Sun Yat-sen University Cancer Center between 1998 and 2012 were included in this retrospective study. The key prognostic factors affecting survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 16 publications
(34 reference statements)
1
26
0
8
Order By: Relevance
“…Wilkie et al 2 suggested using margins for cutaneous squamous cell carcinoma, specifically those that are 4–6 mm in size. Zhuang et al 16 showed improved overall survival in their study when a surgical margin of 1 cm was taken. Mohs micrographic surgery could also be used for excision of TC, as it allows for immediate assessment of surgical margins while preserving as much normal tissue as possible; Kim et al 17 reported no recurrence in 19 months of follow-up when using Mohs micrographic surgery for excision of TC.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Wilkie et al 2 suggested using margins for cutaneous squamous cell carcinoma, specifically those that are 4–6 mm in size. Zhuang et al 16 showed improved overall survival in their study when a surgical margin of 1 cm was taken. Mohs micrographic surgery could also be used for excision of TC, as it allows for immediate assessment of surgical margins while preserving as much normal tissue as possible; Kim et al 17 reported no recurrence in 19 months of follow-up when using Mohs micrographic surgery for excision of TC.…”
Section: Discussionmentioning
confidence: 94%
“…The characteristically indolent nature of TC suggests that a cure is possible with wide local excision 16. There is no current consensus on surgical margins or follow-up for patients with TC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoma Triquilemal é uma lesão maligna rara a qual se origina de células do folículo piloso (bainha externa da raiz do folículo capilar). Acomete indivíduos de ambos os sexos entre 40 e 90 anos de idade 1,3,5,6,7 .…”
Section: Introductionunclassified
“…Não há na literatura tratamento padrão para metástase, porém, alguns sugerem regime quimioterápico para as metástases, como cisplatina e ciclofosfamida (levando à remissão parcial, e não à cura) 3 .…”
Section: Introductionunclassified